A Novel Routing Control Technique for the Energy Hole in the Underwater Acoustic Distributed Network. (18th February 2021) - Xiao, Dong; Zhao, Min; Jia, Ning; Peng, Tong-Rui; Chen, Yan; Ma, Li
Abstract : The energy hole is a severe problem for underwater acoustic distributed networks in that it affects the normal operations of the network and shortens the network's life span. To deal with this problem, a loop-free routing control technique is proposed in this paper. The classical shortest-path routing control method is used to generate multiple disjointed routing tables. The residual energy of the nodes and the changing information of the uplink/downlink matrix are added to the data frames for distribution. The source node specifies the routing path to transmit the data frames based on the changing information, and the relay nodes route the data frames strictly according to the routing path designated by the source node. Besides, the energy consumption of the relay node is saved by replying to the pseudo-ACK frame. Simulation experiments are implemented in four typical scenarios, and the results reflect that the proposed technique could extend the network's life span by approximately 10% when compared to other mature techniques. Besides, it has no other negative effects on the normal operations of the network.